Dynamic power management and adaptive packet size selection for IoT in e-Healthcare. (January 2018) - Chen, Xi; Ma, Ming; Liu, Anfeng
Highlights: A global link decision (GLD) scheme is proposed to decide power and packet size over links. GLD scheme is a strategy which can optimize multiple performances at the same time. GLD scheme is proved to simultaneously improve transmission reliability by 8.7% and decrease delay by 7.7% under same lifetime. GLD scheme is more effective which richly balances distribution of consumed energy in case waste. Abstract: Wireless communications in e-healthcare must work in a reliable, fast and energy-efficient fashion. In this paper, first, a power level decision (PLD) algorithm is proposed to select the optimal power level for each node, which enables the minimum energy consumption on transmitting data per bit. Second, a power level and packet size decision (PPD) algorithm is presented to decide the optimal packet size, by either minimizing the delay at a prescribed transmission power or minimizing energy consumption with a prescribed delay. Third, a global link decision (GLD) scheme is devised to improve overall reliability and decrease overall delay simultaneously through raising availability of battery energy within nodes. Theoretical analysis demonstrated the validity of the GLD scheme. Moreover, experimental results show that the GLD scheme improves the transmission reliability by 8.70% and decreases the delay by 7.74%, without reducing the network lifetime, which was not achieved in previous research studies. Graphical abstract: The wireless sensor network application scene for hospital